Intranasal cocaine in humans: Effects of sex and menstrual cycle - Collins, Stephanie L.; Evans, Suzette M.; Foltin, Richard W.; Haney, Margaret (Pharmacology, biochemistry and behavior, 2007)
Studies have shown that smoked and intravenous cocaine's effects differ in cocaine-dependent women compared to men and across the menstrual cycle. However, this has not been systematically investigated with intranasal cocaine. Thus, a range of intranasal cocaine doses was examined in cocaine-dependent women across the menstrual cycle. Female cocaine users were admitted to the hospital once during the luteal phase and once during the follicular phase of their menstrual cycle; menstrual cycle phase during admissions was counterbalanced. During each admission, an intranasal cocaine dose–response curve (0.06, 0.34, 0.69 and 1.37 mg/kg) was determined during four laboratory sessions. Cocaine produced similar dose-related increases in ratings of “positive” subjective effects, cardiovascular effects and cocaine plasma levels in women in both menstrual cycle phases. To assess sex differences in the effects of intranasal cocaine, the current data were compared to published data collected in men using an identical procedure. Cocaine produced similar dose-related increases in ratings of positive subjective effects, cardiovascular effects and cocaine plasma levels in men and women. Thus, in contrast to studies examining smoked or intravenous cocaine administration, there were no sex differences or menstrual cycle effects on the subjective or cardiovascular response to intranasal cocaine, suggesting that the influence of sex and menstrual cycle on cocaine's effects vary as a function of route of administration.